The effect of board of directors characteristics on risk and bank performance: Evidence from Turkey - Doğan, Berna; Ekşi, İbrahim Halil (Economics and Business Review, 2020)
A bank, particularly in developing countries like Turkey, is one of the mostimportant institutions in the financial sector. Therefore knowing the factors affectingthe performance of banks is important for the development of the sector. One of thefactors affecting the risk and profitability of banking sector is the internal factors ofthe banks. The aim of this paper is to investigate the board of directors’ characteristicsand its effect on risk level measured by non-performing loans and on bank performancemeasured by asset profitability using the Generalized Method of Moments(GMM) estimator. Data from nineteen deposit banks for the period 2012–2018 wereused. The result of the study determined that the board size, foreign board membersand the independent board members have an effect on both non-performing loansand the return on assets.